Features of Plasma Electrolytic Formation of Manganese- and Cobalt-Containing Composites on Aluminum Alloys - Ann V. Karakurkchi; Nykolay D. Sakhnenko; Maryna V. Ved’; Ihor S. Luhovskyi; Hryhoriy A. Drobakha; Maryna V. Mayba (Advances in Materials Science and Engineering)
This paper presents the results of studies on the electrochemical treatment characteristics of aluminum and alloys in alkaline electrolytes. It is shown that the heterogeneity of the alloys composition complicates the formation of the surface oxide layer. To homogenize the treated surface and obtain oxide coatings doped with manganese and cobalt, electrolytes based on KOH and K4P2O7 with the addition of KMnO4 and CoSO4 were used. Plasma electrolytic oxidizing (PEO) in these electrolytes in the range of current densities 5–20 A/dm2 allows to obtain mixed oxide coatings which contained both aluminum oxide matrix and doping metal oxides Al2O3·MnOx and Al2O3·CoOy. It is shown that an increase in the PEO current density and the concentration of manganate- and cobalt(II) ions in the solution leads to an increase the content of dopant metals in the coatings outer layer. The incorporation of manganese and cobalt oxides in the composition of the surface layers was confirmed by the results of X-ray structural analysis. The rational modes of aluminum alloys PEO treatment were substantiated to obtain coatings with manganese and cobalt contents up to 25–40 аt.%. Formed oxide systems have a developed surface and high adhesion to the base metal and show an increased corrosion resistance and catalytic activity. This allows us to view them as promising materials for air- and water-cleaning technologies and internal combustion engine waste gas purification systems.